Determinants of Earning Management at Indonesias Coal Mining Companies - Fitri, Euis Nessia; Hakim, Dani Rahman (JIFA (Journal of Islamic Finance and Accounting), 2021)
This study analyzes the determinant of earning management based on profitability, firm size, institutional ownership, and audit committee on Indonesia's mining sector companies. This study uses panel data from the 2014-2019 financial report of 9 mining companies listed on the Indonesia Stock Exchange (IDX). The sample is determined by the purposive method, which resulted in 54 observations data. Using the common effect model (CEM) panel data analysis, this study has revealed that firm size and audit committee has a negative, but institutional ownership has a positive effect on earning management. Besides, profitability does not affect earning management. This study implies that companies need to improve their monitoring quality by adding more audit committee to reduce the earning management. The government is expected to facilitate the role of institutional investors so that they can be more optimal in the aspect of supervision, not just profit orientation. Future studies are expected to increase the number of data observations, variables, and more method to obtain the robustness result about earning management determinants.